Is arthroplasty necessary after sternoclavicular tumor resection? - Li, Yang; Gao, Erji; Yang, Yi; Gao, Zongli (Journal of Thoracic Disease, 2019)
The diagnosis and treatment of tumors involving the sternum are managed by thoracic and those of tumors of the clavicle by orthopedic surgeons. Presently, there are a number of reports documenting sternoclavicular joint reconstruction after sternal tumor resection (1,2). However, the management of clavicular tumors is controversial (3,4). When the lesion involves the sternoclavicular joint, it is often necessary to resect not only parts of the sternum and clavicle but also the sternoclavicular joint. The process of sternoclavicular joint reconstruction is challenging, and the need for it is often questioned by both thoracic and orthopedic surgeons. There is a paucity of literature on this subject. In this report, we retrospectively reviewed 5 patients with sternoclavicular joint pathologies who were treated between 2016 and 2017. By combining our findings with existing reports, we discuss the approaches to the management of this disease.